2018
DOI: 10.1039/c8ra03437k
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced efficiency of Cu2ZnSn(S,Se)4 solar cells via anti-reflectance properties and surface passivation by atomic layer deposited aluminum oxide

Abstract: Reducing interface recombination losses is one of the major challenges in developing Cu 2 ZnSn(S,Se) 4 (CZTSSe) solar cells. Here, we propose a CZTSSe solar cell with an atomic layer deposited Al 2 O 3 thin film for surface passivation. The influence of passivation layer thickness on the power conversion efficiency

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
6
1
Order By: Relevance
“…This suppressed recombination process is one factor leading to V OC enhancement. In summary, in obvious contrast to the interface modification of Al 2 O 3 for kesterite solar cells reported by other researchers, [31][32][33][34] the Al 2 O 3 introduced by the method used in this study can not only optimize the defects but also improve the quality of the absorber bulk.…”
Section: Recombination Analysiscontrasting
confidence: 66%
See 2 more Smart Citations
“…This suppressed recombination process is one factor leading to V OC enhancement. In summary, in obvious contrast to the interface modification of Al 2 O 3 for kesterite solar cells reported by other researchers, [31][32][33][34] the Al 2 O 3 introduced by the method used in this study can not only optimize the defects but also improve the quality of the absorber bulk.…”
Section: Recombination Analysiscontrasting
confidence: 66%
“…It was reported that an Al 2 O 3 layer deposited by ALD on the surface of the absorber layer can reduce the defect density at the CZTSSe/CdS interface [31] or decrease the reflectance from the surface of the absorber. [33] Hao's group at UNSW in Australia think such passivation is from the hydrogen during the deposition of the ALD-Al 2 O 3 layer rather than from Al 2 O 3 . [32,34] Thus, it can be concluded that Al 2 O 3 deposited between the absorber layer and buffer layer can improve the performance because of passivation of the defects, no matter whether it is due to Al 2 O 3 or hydrogen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the photoresponse of the fabricated device enhanced in the entire visible region as well as in longer wavelengths (600−1000 nm) with better carrier separation that suggests an improved rear-interface with reduced recombination. 40 The improvement in the CZTSSe absorber quality observed in FESEM images supports the enhancement in the EQE spectra after inserting the CAO nanolayer. Besides, Table S2 summarizes the performance of kesterite TFSCs based on previously reported various passivation layers for the rear interface (Supporting Information).…”
Section: Resultsmentioning
confidence: 53%
“…Using a suitable passivation layer can reduce the MoS/Se 2 layer thickness. Various passivation layers have been effectively applied to reduce the thickness of MoS/Se 2 , including Al 2 O 3 , [59,60] MoO 3 , [61] Bi, [62] Ti, [63] CuO, [64] SnO 2 , [65] MoO 2 , [66] carbon, [67,68] graphene oxide, [69] TiN, [70,71] ZnO, [72,73] Ag, [74] TiB 2 , [75] CuAlO 2 , [76] CuGaSe 2 , [77] Al-doped ZnO, [78] Na 2 S, [79,80] etc. [36] The abovementioned back-electrode intermediate layers at the Mo/CZTSSe interface effectively control the Mo(S,Se) 2 layer thickness and offer lower resistance at the back electrode.…”
Section: Kesterite-based Tfscsmentioning
confidence: 99%